FEASIBILITY STUDY OF THE 2.7–2.9 GHZ FREQUENCY BAND FOR S-BAND WEATHER RADAR: OPERATIONAL AND REGULATORY PERSPECTIVES IN INDONESIA - Maulana Putra; Sugiarto; Nasrul Wathon; Hanif Andi Nugraha (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Weather radar is a vital component of atmospheric observation systems, particularly in tropical regions such as Indonesia that are highly vulnerable to extreme rainfall. The S-band frequency range is well known for its low rain attenuation and favorable propagation stability, making it suitable for long-range weather monitoring. However, the expansion of International Mobile Telecommunications (IMT) services in adjacent frequency bands introduces challenges related to spectrum coexistence and potential interference that require comprehensive assessment. This study evaluates the technical feasibility and regulatory compatibility of the 2.7–2.9 GHz frequency band for S-band weather radar operation in Indonesia by considering tropical rainfall characteristics, electromagnetic wave propagation, and national spectrum management dynamics. The analysis employs rain attenuation and rainfall distribution models based on ITU-R recommendations, along with a review of national and international spectrum regulations, including an assessment of potential interference from IMT systems through unwanted emission and emission mask analyses. The results indicate that S-band weather radar operating at 2.7–2.9 GHz exhibits low rain attenuation under high-intensity rainfall conditions and is capable of maintaining wide-area observational coverage. From a regulatory perspective, this frequency band is formally allocated and enables safe spectrum coexistence with IMT systems through the application of protection criteria, unwanted emission control, and appropriate guard band arrangements.